Qualitative analysis of the perceptions of rural communities about the use of awareness‐raising videos in nutrition and health programs in Benin - Bodjrenou, Sam; Amoussa Hounkpatin, Waliou; Bada, Merveille; Vodouhe, Simplice; Termote, Céline; Savy, Mathilde (Wiley, 2023)
This cross-sectional study aims at analyzing the perceptions of mothers, community leaders, and nutrition/health care workers (NHCWs) about using videos in nutrition and health programs compared to posters. In total, we recruited 42 mothers, 39 community leaders, and 30 NHCWs from villages and local organizations in two rural districts in South Benin, Bopa, and Houéyogbé. Learning sessions on Dietary diversity and Hygiene and deworming were organized using posters and videos. Participants' opinions on pros and cons of videos and posters were collected using individual semi-structured interviews with NHCWs and focus group discussions with mothers and community leaders, then analyzed thematically. Results showed that videos were perceived as more adapted to rural communities than posters because they were in local languages, self-explanatory, appealing, and captivating. Videos also enabled the dissemination of standardized messages. Globally, participants better-understood messages from videos than from posters, especially when dealing with dynamic processes. However, the speed of video sequences allowed limited time for self-reflection and assimilation of certain messages. The absence of electricity and lack of equipment to play videos in villages are also major constraints on the use of videos in such settings. While videos are innovant communication tools that should be promoted to improve motivation and compliance in learnings, they should be preferably used as complements to traditional posters for optimized assimilation of messages.